Burdock Fructooligosaccharide Attenuates High Glucose-Induced Apoptosis and Oxidative Stress Injury in Renal Tubular Epithelial Cells - Ding, Mengru; Tang, Zhiyan; Liu, Wei; Shao, Taili; Yuan, Pingchuan; Chen, Kaoshan; Zhou, Yuyan; Han, Jun; Zhang, Jing; Wang, Guodong (Frontiers in Pharmacology, 2021)
Hyperglycemia-induced apoptosis and oxidative stress injury are thought to play important roles in the pathogenesis of diabetic nephropathy (DN). Attenuating high glucose (HG)-induced renal tubular epithelial cell injury has become a potential approach to ameliorate DN. In recent years, burdock fructooligosaccharide (BFO), a water-soluble inulin-type fructooligosaccharide extracted from burdock root, has been shown to have a wide range of pharmacological activities, including antiviral, anti-inflammatory, and hypolipidemic activities. However, the role and mechanism of BFO in rat renal tubular epithelial cells (NRK-52E cells) have rarely been investigated. The present study investigated the protective effect of BFO on HG-induced damage in NRK-52E cells. BFO could protect NRK-52E cells against the reduced cell viability and significantly increased apoptosis rate induced by HG. These anti-oxidative stress effects of BFO were related to the significant inhibition of the production of reactive oxygen species, stabilization of mitochondrial membrane potential, and increased antioxidant (superoxide dismutase and catalase) activities. Furthermore, BFO increased the expression of Nrf2, HO-1, and Bcl-2 and decreased the expression of Bax. In conclusion, these findings suggest that BFO protects NRK-52E cells against HG-induced damage by inhibiting apoptosis and oxidative stress through the Nrf2/HO-1 signaling pathway.